(untitled) (Research, Society and Development, 2022)
Phytoremediation is an innovative, efficient and eco-friendly technique for the treatment of contaminated areas. This method consists in the use of plant species for extraction, degradation, containment or immobilization of pollutants/xenobiotics. Recently, ornamental plants have been gaining spotlight in remediation studies, precisely because of their aesthetic value and their ability to develop in environments contaminated with heavy metals, textile dyes and pesticides. An important ornamental species for these studies is Zantedeschia aethiopica (L.) Spreng. popularly known as calla lily. The objective of this narrative review is to report up-to-date studies on the use of phytoremediation to clean up contaminated areas and highlight the use of ornamental plants of the genus Zantedeschia in this process, especially the species Zantedeschia aethiopica. For this, articles indexed between 2015 and 2022, written in Portuguese and English, were selected and the searches were carried out through three electronic databases, Google Scholar, Web of Science and SciELO. The papers were selected through the association between the words Zantedeschia spp., Zantedeschia aethiopica, ornamental plants and phytoremediation with several other related topics. This review aims to emphasize the gaps found in phytoremediation of contaminated environments studies, specially mediated by Z. aethiopica, indicating paths for further research.